The Influence of Blockchain Technology on the Level of Transparency and Accountability of Financial Management of Student Organizations at the Faculty of Economics and Business, University of Muhammadiyah Makassar - Ayu Eka Wardani; Muchriana Muchran (IECON: International Economics and Business Conference, 2024)
This study aims to examine the influence of blockchain technology on transparency and accountability in financial management of student organizations at the Faculty of Economics and Business, University of Muhammadiyah Makassar. Blockchain technology offers innovative solutions in financial management by providing a transparent, secure, and hard-to-manipulate record-keeping system. This study uses a quantitative method with data collected through a survey of 40 respondents involved in the financial management of student organizations. Data analysis was conducted using multiple linear regression to evaluate the relationship between blockchain technology variables, transparency, and accountability. The results show that blockchain technology and transparency significantly affect accountability. An R² value of 0.735 indicates that 73.5% of the variation in accountability can be explained by these two independent variables, while the remaining 26.5% is influenced by other factors outside the model. This research makes an important contribution in supporting the adoption of blockchain technology as a tool to improve the transparency and accountability of student organization financial management, while strengthening better organizational governance.